Força muscular e desempenho físico : um estudo com idosos de centros de convivência - Penteado, Dayane de Carvalho Rodrigues (2022)
The increase in life expectancy from technological and scientific advances related to health and improvement of quality of life has contributed to the growth of the elderly population in the world scenario, active and healthy aging being the great challenge in this process. Thus, it is evident the need to develop studies that address aspects of functionality and health of the elderly population. Aging causes physiological and metabolic changes that lead to decreased function and reduced muscle strength, central themes of this thesis. Functional capacity is influenced by genetic factors and has as a strong predictor physical performance, also being determined by sociodemographic, economic, psychological, presence of morbidities, lifestyle behaviors and nutritional factors. This thesis presents two scientific manuscripts as products. The first manuscript aimed to analyze the association between anthropometric markers and handgrip strength in the elderly. This is a cross-sectional study with 485 elderly of both sexes and age ≥ 60 years. The anthropometric markers evaluated were: Body Mass Index, Mid-upper Arm Circumference and Calf Circumference. Handgrip strength (HGS) was measured by means of a hydraulic dynamometer manual Jamar®, accepted as a reference instrument for assessing the grip force. Anthropometric markers were measured using standardized techniques and sociodemographic, economic and lifestyle data were collected by trained interviewers. Generalized linear models (GLM) with log link and gamma family were used to analyze the association of anthropometric markers with maximum HGF. Directed acyclic graph (DAG) was constructed to identify potential confounding factors. The calf circumference remained associated with maximal HGS, after adjusting for potential confounding factors. For each centimeter increased in the calf, HGS increased 4% (β= 1.04, 95%CI: 1.03;1.07) in men and 1% (β= 1.01, 95%CI: 1.00;1.02) in women. The second manuscript estimated the prevalence of poor physical performance and associated factors in elderly women. Physical performance was assessed by the Short Physical Performance Battery (SPPB), which provides an objective measure of physical performance, based on physical tests. The associated factors were assessed by a questionnaire that included sociodemographic, economic, lifestyle behaviors and weight and health conditions. The association between the independent variables and the low physical performance was estimated by adjusted Poisson regression models with robust variance, adopting the hierarchical input of variables in the model. The prevalence of poor physical performance among the elderly was 44.0%. The variables associated with poor physical performance were: age ≥ 70 years, low education, sedentary behavior, low handgrip strength and diabetes mellitus. In conclusion, the study results confirmed the association of calf circumference with HGS, regardless of potential confounding factors, in both sexes. The prevalence of low physical performance was high and associated with variables of different levels of determination among elderly women. This information can be useful in planning public policies for healthy aging.